2006
DOI: 10.1287/mnsc.1060.0530
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Gathering, Team Capabilities, and Project Performance in Challenging Work Environments

Abstract: Knowledge gathering can create problems as well as benefits for project teams in work environments characterized by overload, ambiguity, and politics. This paper proposes that the value of knowledge gathering in such environments is greater under conditions that enhance team processing, sensemaking, and buffering capabilities. The hypotheses were tested using independent quality ratings of 96 projects and survey data from 485 project team members collected during a multi-method field study. The findings reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
131
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(136 citation statements)
references
References 52 publications
4
131
0
1
Order By: Relevance
“…In contrast, several of the studies cited above offered evidence to suggest that a personalized or socialized power orientation can be cued by an experimenter or by characteristics of the situation (e.g., Overbeck & Park, 2001, 2006Ven der Vegt et al, 2009). …”
Section: Direction #4: the Antecedents Of A Socialized Power Orientationmentioning
confidence: 98%
See 1 more Smart Citation
“…In contrast, several of the studies cited above offered evidence to suggest that a personalized or socialized power orientation can be cued by an experimenter or by characteristics of the situation (e.g., Overbeck & Park, 2001, 2006Ven der Vegt et al, 2009). …”
Section: Direction #4: the Antecedents Of A Socialized Power Orientationmentioning
confidence: 98%
“…Those lower in the social hierarchy are less goal-directed because they lack a sense of control and must keep track of more potential threats in their social environment (Guinote, 2007). As a result, they pay attention to more of their social environment but fail to separate peripheral from central and goal-relevant from goal-irrelevant aspects of that environment (Overbeck & Park, 2001, 2006Smith, et al, 2008).…”
Section: Socialized Power and Anchoring On Shared Goalsmentioning
confidence: 99%
“…The provision of tools and systems that automate administrative tasks (such as setting meeting times or distributing announcements) also can help to moderate levels of context switching and temporal misalignment. Third, managers defining different types of roles on a team -e.g., whether a member is core or peripheral, or a "consultant" versus a major contributor -can help employees prioritize their time and set expectations about meeting attendance (Ancona & Bresman, 2007;Haas, 2006). Fourth, understanding the attributes of individuals and of project structures that best lend themselves to an MTM environment can increase the probability of success.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…An important way in which organizations avoid errors is through knowledge sharing (Cummings 2004, Haas 2006. However, studies have found that transmission of knowledge within organizations is negatively affected by geographic distance between individuals (Allen 1977).…”
Section: Theory and Hypothesesmentioning
confidence: 99%